(untitled) (Journal of Engineering, 2005)
procedure is presented to calculate an equivalent diameter for soil grains to be used to calculate the specific surface of the soil. The typical grain size distribution curve is expressed as a normal probability distribution cumulative curve and the frequency corresponding to the equivalent diameter is accordingly found. This frequency is adopted as the percent finer corresponding to the equivalent diameter. A relation is given for the calculation of the specific surface using the equivalent diameter. Grain size distribution curves of many soil samples are collected. A value for the specific surface of each soil is determined summing the surface area of subintervals in the distribution curve. The values of specific surface obtained from these gradation curves are compared to those calculated using the proposed values of the equivalent diameter for each soil.